An Afrocentric Critique of World Systems Analysis as a Critical Theory in International Relations - Makhura Rapanyane; Kgothatso Shai (African Journal of Political Science)
In this research paper, authors provide a comprehensive overview and critique of the World System Analysis (also read as World System theory). This central focus is driven by the need to bring about a fair and justifiable explanation of the theory and appreciation by examining the work critically as the most persuasive theory in international relations. The aim of this paper is to bring about world system analysis as the best tool in analysing the world politics, understanding world history and key reasons for imperialism, and why core countries such as the United States of America (USA), China and etc., often intervene in world crises through grants and other forms of aid. The authors argue that the world system theory, unlike the dependency theory, is broader in perspective and place the world as a centre of attention in the analysis of the world economic distribution instead of the nation-state. Equally, it can also be deployed in understanding global inequality, dependency and power. The above argument which is achieved through the use of a qualitative approach that has taken the form of the adoption of secondary materials and the Afrocentric paradigm.